Long-time storage effect on the seed heaLth of spring barley grain. - Wiewióra, Barbara (Plant Breeding and Seed Science, 2009)
Seeds of 5 cultivars of spring barley, originated from field experiments conducted in 2000 at Radzików, were tested immediately after harvest and after three, four and five years of storage in uncontrolled conditions, for incidence of seed-borne fungi with special regard to “field fungi” (Bipolaris sorokiniana and Fusarium spp.) and "storage fungi" (species of Penicillium and Aspergillus). The studies showed that barley seeds were infected before storage by numerous fungi as well as the saprophytes: Alternaria alternata, Acremonium spp., Acremoniella atra and the pathogens: Bipolaris sorokiniana and ten Fusarium species. The analysis after storage showed that the frequency of fungal infection had changed. The occurrence of some fungi was significantly affected by the period of storage...